2008
DOI: 10.1007/s11581-008-0307-z
|View full text |Cite
|
Sign up to set email alerts
|

The production of nickel–alumina composite coating via electroplating

Abstract: A series of electroplating works have been conducted to investigate the best condition for the coelectrodeposition of nickel-alumina (Ni/α-Al 2 O 3 ) composite coating. Co-electrodeposition was done onto mild steel as cathode at ambient temperature (27°C) with current density of 30 mA/cm 2 under α-Al 2 O 3 concentration of 2 g/l and various agitation speeds of 50, 100, 150, 200, and 250 rpms. The cross-section of the composite coatings portrayed α-Al 2 O 3 particles was co-deposited. Under field emission scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Different amounts of Al 2 O 3 were added to the nickel bath (0-150 g/l) and the suspensions obtained were sonicated for 30 min to disperse the particles and to break up possible solid agglomerates. The suspensions were stirred for 15 min before starting the deposition to ensure uniform dispersion and it was also constantly stirred at 200 rpm during the deposition in order to homogeneously suspend the Al 2 O 3 particles; the same stirring bar was employed in the same geometry for all the experiments in order to assure consistency of the hydrodynamic conditions [43].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different amounts of Al 2 O 3 were added to the nickel bath (0-150 g/l) and the suspensions obtained were sonicated for 30 min to disperse the particles and to break up possible solid agglomerates. The suspensions were stirred for 15 min before starting the deposition to ensure uniform dispersion and it was also constantly stirred at 200 rpm during the deposition in order to homogeneously suspend the Al 2 O 3 particles; the same stirring bar was employed in the same geometry for all the experiments in order to assure consistency of the hydrodynamic conditions [43].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore they investigated the effect of stirring speeds (100-1000 rpm) on the coating composition showing that the speed affected the average size of particle in the deposit [42]. Similarly Badarulzaman et al [43] studied the effect of 'agitation rate' on the deposition process using a magnetic rotating bar with speed rates 50-250 rpm. They found an increase in particle concentration in the coating, as well as coating hardness with increasing speed.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that alumina density increase at bath has boosted hardness of composite coating which is related to more participation of alumina particles in coating. In another research on electrical deposition of Ni/ Al 2 O 3 with revolving multidimensional electrode, effect of density of alumina particles was studied on particles volumetric percentage in coating [39,[44][45][46][47][48][49][50][51][52][53][54][55][56][57]. …”
Section: Effect Of Density Of Alumina Nanoparticles In Electrolyte Bathmentioning
confidence: 99%
“…Command washcoat material such as Al 2 O 3 , SiO 2 , TiO 2 , or SiO 2 -Al 2 O 3 [7]. However, γ-Al 2 O 3 washcoat material not fully explored even though it promising several advantages such as low price, high surface area, good chemical stability, high micro-hardness, and wear resistance at high-temperature [8]. Therefore, in this research the FeCrAl is coated by γ-Al 2 O 3 powder which can result higher surface area of about 100 m 2 /g.…”
Section: Introductionmentioning
confidence: 99%